Analisis Perubahan Perilaku Konsumen di Era Pasca Pandemi terhadap Belanja Online - Ibrahim, Darmawansah (Jurnal Ilmiah Manajemen & Kewirausahaan, 2024)
This study aims to analyze changes in consumer behavior toward online shopping in the post-COVID-19 pandemic era. The pandemic has brought significant transformations in consumption patterns, where purchasing activities that were previously dominated by conventional methods have shifted to digital platforms. This research employs a descriptive quantitative method by collecting data through questionnaires distributed to 150 e-commerce users in Indonesia. The results show that the main factors influencing the increase in online shopping behavior after the pandemic are ease of access, trust in digital platforms, and new habits formed during social restrictions. Consumers are now more concerned with transaction security, delivery speed, and user reviews before making a purchase. In addition, the study found that consumer loyalty toward online brands has increased along with positive shopping experiences and responsive after-sales services. The study concludes that changes in consumer behavior in the post-pandemic era are permanent in several aspects, indicating that businesses must adapt their digital marketing strategies to retain and enhance customer loyalty in an increasingly competitive online market.